2001
DOI: 10.1046/j.1365-2222.2001.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of conformational and linear epitopes in the achievement of tolerance in cow's milk allergy

Abstract: Patients with persistent milk allergy possess higher detectable levels of IgE antibodies to linear epitopes from alpha(s1)- and beta-casein than children who have achieved tolerance. Specific IgE binding to particular linear epitopes in alpha(s1)-casein may be a predictive factor for persistence of CMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(143 citation statements)
references
References 24 publications
2
133
1
5
Order By: Relevance
“…Differences in recognition of specific epitopes have been described previously between patients with transient and persistent cow's milk allergy (14,19,35,36). It appeared that patients with persistent cow's milk allergy showed more frequent and more intense IgE reactivity and mediator release to r␣S1-casein and ␣S1-casein-derived peptides than did patients who had outgrown milk FIGURE 9.…”
Section: Discussionmentioning
confidence: 70%
“…Differences in recognition of specific epitopes have been described previously between patients with transient and persistent cow's milk allergy (14,19,35,36). It appeared that patients with persistent cow's milk allergy showed more frequent and more intense IgE reactivity and mediator release to r␣S1-casein and ␣S1-casein-derived peptides than did patients who had outgrown milk FIGURE 9.…”
Section: Discussionmentioning
confidence: 70%
“…It has been described that some children who are allergic to HE are able to tolerate this food cooked but not raw (15). As suggested by Vila et aI., during food processing, heat and/or chemical processes can modify or disrupt many conformational epitopes, exposing linear epitopes (16). Moreover, Cooke & Sampson suggest that the development of IgE antibodies to these linear epitopes can be related to the persistence of HEA (17).…”
Section: Figures Indicate MM (Mean Oforthogonal Wheals Diameters)mentioning
confidence: 96%
“…Recent studies have demonstrated that the persistency of CMA is associated with differences in IgE-binding epitopes to the different cow's milk proteins (CMPs). 3,4 Because T cells are responsible for the isotype switching of antigen-specific B cells to IgE, T-cell activation is the initial step in determination of the outcome of the immune response and plays a major role in the maintenance of the reaction. This might suggest that the observed differences in IgE-binding epitopes could be reflected in the CMPspecific T-cell pool.…”
mentioning
confidence: 99%